FOOD AND FEEDING BIOLOGY OF A TROPICAL FRESHWATER CATFISH, MYSTUS NEMURUS C. & V. WITH REFERENCE TO ITS FUNCTIONAL MORPHOLOGY - Khan, M S; Ambak, M A; Mohsin, A K M (Indian Journal of Fisheries, 2011)
The food, feeding biology and the morphology of associated organs of a tropical catfish, Mystus nemurus C. & V. were studied for one year. A total of 267 specimens of M. nemurus C. & V. were examined. Results indicate that they are usually euryphagous, feeding extensively on a wide variety of food items in the bottom substrate of the reservoir. This is clearly reflected in the morphological and anatomical characteristics of various organs concerned with feeding. Adult specimens feed predominantly on teleosts followed by crustaceans and insects. Aquatic vegetations and detritus are swallowed as accidental food items. Feeding intensify as they approach size of first maturity. Relative gut indices change insignificantly from young of year to adult stage and are insignificant (p > 0.05). Symptoms of gastric regurgitation were not evident.